تحسين القساوة وصلابة الصدم لسبيكة ألمنيوم 2014 باستخدام التعتيق المتقطع T6i6 - علي هترة; خليل عزيمة; آرام عبد الرحيم (Tishreen University, 2019)
إنّ هدف هذا البحث هو دراسة تأثير التعتيق في صلابة الصدم لسبيكة  2014  Al-Cu-Mg . بعد  التخمير الانتشاري solution treatment  إلى درجة °C493 والإبقاء لمدة ساعة عند هذه الدرجة، ومن ثم الإسقاء في الماء، عتقت العينات بعد ذلك عند درجة  °C150 لفترات مختلفة (من 1 حتى h 18) خلال فاصل زمني متضاعف لوغارتميا . ضبطت مراحل الترسيب في أثناء التعتيق بقياسات القساوة. لكلّ مجموعة عينات، نفذت اختبارات القساوة وصدمIzode  . تزايدت أولا بعد التعتيق صلابة الصدم  للسبيكة ،و تبعه بعد ذلك، هبوط حاد بسبب ترسب الأطوار الوسيطة، أخيرا وصل إلى حدّه الأدنى في ذروة القساوة. نوقشت الارتباطات بين القساوة، وصلابة الصدم للعينات المدروسة. The aim of this study is to investigate the effect of aging on the toughness impact of 2014 Al-Cu-Mg alloy. Following the 1 h solution zing treatment at 493°C and water quench, the specimens were aged at 150°C for various periods (1 to 18 h). The precipitation stages during aging were monitored by hardness measurements. For each specimen group, Izode impact and hardness tests were carried out. During aging, the toughness impact of the alloy first increased, and then, followed a maximal decrease due to the precipitation of intermediate phases; finally it reached a minimum at the peak of hardness. The correlations between hardness and toughness impact were also investigated.